Research of Phenomenon of Synchronous Lateral case: "Rayitos de Sol" Footbridge - León Deza, Julio Alfredo (2020)
In the last decades, numerous footbridges experienced excessive displacements in the lateral direction of passage, cases such as Millennium, Solferino and Toda among the most known, which caused that the pedestrian have difficulties in using these structures and often requiring expensive repairs. This research studies the problem of the lateral vibrations produced by the pedestrian crossing in footbridges known as the phenomenon of synchronous lateral excitation through the lateral vibration analysis of the walkway adjacent to the “Rayitos de Sol” footbridge, which crosses the Rímac river, near the center of Lima. This particular footbridge had presented excessive lateral vibrations from its construction in 2006, until 2016 when this research was developed. This particular situation constituted an ideal state for the development of experimental work. Particular details of the phenomenon of synchronous lateral excitation were found during this research.  first, that the pedestrian density is directly proportional to the probability of occurrence of the phenomenon, second, that the phenomenon is cyclic in nature and the occurrence of a maximum acceleration from which the pedestrian breaks its path and the phenomenon decays.